DIGITAL TRANSFORMATION IN PUBLIC SERVICES CHALLENGES AND OPPORTUNITIES: BANGKOK’S SMART CITY DEVELOPMENT - Binsumsuree, Wilaiporn (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the effectiveness, challenges, and opportunities associated with the digital transformation of public services in Bangkok, particularly within the context of smart city initiatives. It emphasizes the role of digital tools in enhancing urban management, accessibility, and citizen participation. Method: Employing a mixed-methods approach, the research integrates quantitative surveys and qualitative interviews with citizens, public sector employees, and policymakers to investigate perceptions, technological readiness, and existing digital skill gaps. Results: The findings reveal that while digital initiatives—such as smart traffic systems and e-Government services—have shown promise in improving urban functionality and community engagement, their implementation is hindered by resistance to change, insufficient digital literacy, and limited infrastructure and funding. Novelty: This study contributes to the literature by focusing on the real-world application of smart city technologies in a rapidly developing digital metropolis. It uniquely evaluates how digital platforms facilitate civic collaboration and proposes strategic recommendations to overcome existing barriers. The research highlights Bangkok's potential to become a model smart city by promoting innovation, strengthening infrastructure, and enhancing digital competencies among stakeholders.